Experimental Study on Diesel Motor Performance Using Dimethyl Ester Mixture With Diesel - Muhammad Iqbal (International Journal of Mechanical Computational and Manufacturing Research, 2022)
Scarcity of fuel oil (BBM) which occurs encouraging research to develop alternative fuel sources as a substitute for diesel fuel. Based on these ideas, testing TecQuipment type.TD4A 001 diesel engine using biodiesel fuel from palm oil. In this test biodiesel derived from palm oil through the process of esterification and transesterification in ester form dimethyl. The purpose of this study was to determine the performance of the biodiesel-fueled engine dimethyl ester so it will look its effect on diesel engine performance parameters, especially reducing the content of the resulting exhaust emissions of diesel engine. This study will also provide information as a reference for the education world who wants to do research in the field of automotive in the development of biodiesel fuel and its effect on the performance of diesel engine. Biodiesel is a diesel motor fuel in the form of alkyl ester /alkyl acids - fatty acids called vegetable oil through a process of esterification. The term biodiesel is identical to the pure fuel. Biodiesel blends (Bxx is xx percent biodiesel mixed with diesel number 1-xx percent). Supposed Fuels Biodiesel (B10) containing 10% biodiesel Dimethyl Ester, 90% Diesel. Biodiesel is an alternative diesel fuel made from natural resources such as renewable, palm, castor, pecans, etc. The use of biodiesel as diesel fuel does not require modifications to the vehicle's engine. Biodiesel can be blended with diesel fuel at a certain ratio. With the use of biodiesel has the potential to reduce exhaust emissions. Using the use of biodiesel as a fuel engine will provide many advantages of the diesel engine performance.